Analysis The Influence of Interest In Using Gopay Application With The DeLone and McLean Method In The City of Batam - Nicholas Jeonanto; Yefta Christian (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2024)
Gopay is a popular digital wallet application in Indonesia, provides convenience for various online transactions such as payments, money transfers, and shopping. Objective of this study is to examine the influence of user interest on the Gopay application using his DeLone and McLean method in the Batam city. Using a quantitative approach, the research was conducted by distributing questionnaires to 385 Gopay users. This study uses DeLone and McLean’s model. This model encompasses five variables: system quality, information quality, service quality, usage, and user satisfaction. Data validity and reliability were tested using SPSS 26, and while hypothesis testing was conducted using the SEM AMOS application. The findings of this analysis indicate that all variables have a positively and significantly contribute to users’ satisfaction with Gopay. This study research provides theoretical and practical implications for digital wallet application developers and researchers conducting similar analyses in the future.